2004
DOI: 10.1111/j.1752-0606.2004.tb01242.x
|View full text |Cite
|
Sign up to set email alerts
|

Treating Intimate Partner Violence Within Intact Couple Relationships: Outcomes of Multi‐couple Versus Individual Couple Therapy

Abstract: An experimental design was used to determine outcomes of a domestic violence-focused treatment program for couples that choose to stay together after mild-to-moderate violence has occurred. Forty-two couples were randomly assigned to either individual couple or multi-couple group treatment. Nine couples served as the comparison group. Male violence recidivism rates 6 months after treatment were significantly lower for the multi-couple group (25%) than for the comparison group (66%). In contrast, men in the ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
151
3
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(167 citation statements)
references
References 21 publications
9
151
3
4
Order By: Relevance
“…The obtained results of study indicated that training of cognitive behavioral skills could significantly effect on reduction of marital conflict and burnout and this result is coordinated with results obtained from studies of Arieta (2008), Chang (2003), Stiths (2004) and Shafeenia and Hosseinian (2007). According to theoretical bases of this study, from the perspective of Seamus the reason for the effect of cognitive behavioral family therapy is that many of cognitive behavioral solutions are applied in this field emphasizing on following options: 1-Determining of family members expectations from each other and their effects on interactions between family members 2-Benefiting from methods leading to increase in abilities of family members to deal with unexpected events, changes and crises (Seamus, 2002) The main reason for the positive effect of cognitive behavioral family therapy on variables of study might have been related to this matter that problems of studies families have been interpersonal not intrapersonal.…”
Section: Discussionsupporting
confidence: 77%
“…The obtained results of study indicated that training of cognitive behavioral skills could significantly effect on reduction of marital conflict and burnout and this result is coordinated with results obtained from studies of Arieta (2008), Chang (2003), Stiths (2004) and Shafeenia and Hosseinian (2007). According to theoretical bases of this study, from the perspective of Seamus the reason for the effect of cognitive behavioral family therapy is that many of cognitive behavioral solutions are applied in this field emphasizing on following options: 1-Determining of family members expectations from each other and their effects on interactions between family members 2-Benefiting from methods leading to increase in abilities of family members to deal with unexpected events, changes and crises (Seamus, 2002) The main reason for the positive effect of cognitive behavioral family therapy on variables of study might have been related to this matter that problems of studies families have been interpersonal not intrapersonal.…”
Section: Discussionsupporting
confidence: 77%
“…The idea that batterers typologies would help develop and match specific treatments to specific subgroups of individuals has been emphasized by a number of researchers (e.g., Cavanaugh & Gelles, 2005;Stith et al, 2004). In fact, Saunders (1996) found evidence that feministcognitive-behavioral treatment (FCBT) tended to result in more positive treatment outcomes (i.e., lower rates of recidivism) for individuals with antisocial personality characteristics, whereas individuals with dependent personality characteristics tended to benefit more from process-psychodynamic treatment (PPT).…”
Section: Clinical Utility Of Batterer Typologiesmentioning
confidence: 99%
“…Thus, although from the reported means, the conjoint condition appeared to be more effective in reducing violence than the GST condition, significant differences were not found. A recent study by Stith et al (2004), which tested individual couple therapy versus multicouple therapy administered after completion of GST, similarly had only a total of 30 couples complete either condition. Couples treatment approaches for partner violence require modification and further testing, including integrating findings regarding women's aggression and dyadic process, and testing in efficacy trials with larger sample sizes before conclusions may be drawn about the efficacy of couples' treatment approaches.…”
Section: Implications For Future Research and Clinical Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the study of Lawson et al 43 , that employed an intervention program based on cognitive behavioural and psychodynamic models, showed an increase in attachment and in global functioning and a decrease in anxiety and depressive symptoms and in violence against the partner or ex-partner. The study conducted by Stith et al 50 , based on couples therapy, also revealed that subjects who participated in the intervention positively changed attitudes towards violence, marital satisfaction and abusive behaviours. Lastly, the research conducted Quasi-experimental (pre-test and post-test) G1 = Secure-changed G2 = Secure-unchanged G3 = Insecure Secure attachment* (+); Anxiety and avoidance attachment: ns; Comfort with closeness and depending of others = G1** (+) x G2 x G3 Avoidance and closeness with others = G1 x G2* (+) x G3* (+); Depression and anxiety* (-) G1* (-) x G2 x G3 Functioning*** (+) G1 x G2 x G3: ns Partner violence* (-) G1 x G2 x G3: ns Lila et al 44 Pre-test and post-test Perceived severity* (+) Responsibility assumption* (+) Risk of recidivism* (-) Lin et al 45 Quasi-experimental (3, 6 and 9 months follow-up) GC = Control Overall violence: GE* (58.6%) x GC (41.4%) (3 months follow-up) Physical violence: GE (20%) x GC (13.4%): ns Verbal violence: GE* (58.6%) x GC (43.7%) (3 months follow-up) Novo et al 26 (Galicia Reeducation Program for Gender Violence Offenders)…”
Section: Methods and Program Efficacymentioning
confidence: 99%